Mechanism of Lethal Skin Toxicities Induced by Epidermal Growth Factor Receptor Inhibitors and Related Treatment Strategies - Li, Yanping; Fu, Ruoqiu; Jiang, Tingting; Duan, Dongyu; Wu, Yuanlin; Li, Chen; Li, Ziwei; Ni, Rui; Li, Li; Liu, Yao (Frontiers in Oncology, 2022)
Epidermal growth factor receptor (EGFR) inhibitors are widely used to treat various types of cancers such as non-small cell lung cancer, head and neck cancer, breast cancer, pancreatic cancer. Adverse reactions such as skin toxicity, interstitial lung disease, hepatotoxicity, ocular toxicity, hypomagnesemia, stomatitis, and diarrhea may occur during treatment. Because the EGFR signaling pathway is important for maintaining normal physiological skin function. Adverse skin reactions occurred in up to 90% of cancer patients treated with EGFR inhibitors, including common skin toxicities (such as papulopustular exanthemas, paronychia, hair changes) and rare fatal skin toxicities (e.g., Stevens–Johnson syndrome, toxic epidermal necrolysis, acute generalized exanthematous pustulosis). This has led to the dose reduction or discontinuation of EGFR inhibitors in the treatment of cancer. Recently, progress has been made about research on the skin toxicity of EGFR inhibitors. Here, we summarize the mechanism of skin toxicity caused by EGFR inhibitors, measures to prevent severe fatal skin toxicity, and provide reference for medical staff how to give care and treatment after adverse skin reactions.